Effect of Extruder Temperature on Dimensional Accuracy and Surface Roughness of Fused Deposition Modeled (FDMed) PLA and PLA/Wood Composite - Juan Pratama; Noverdo Mayanda; Didik Sugiyanto (ROTASI, 2022)
The ability of Fused Deposition Modeling (FDM) 3D printing to create complex products makes this technology increasingly popular and widely used by both hobbyists and even industrial scale. Despite the advantages of FDM technology, the poor dimensional accuracy and surface finish of the FDM-printed product is one of the major drawbacks of this process. Several studies have shown that printing parameters can affect the quality and surface finish of the printed polymers products. In this paper, the effect of extruder temperature on dimensional accuracy and surface roughness of FDM-printed PLA and PLA/Wood composite were investigated through an experimental approach. The results showed that the extruder temperature was proven to affect the roughness and dimensional accuracy of FDM-printed PLA and PLA/Wood composite. The different behavior of polymers and polymer matrix composites concerning temperature variations is evident and briefly discussed.